Port of Sines Terminal XXI: Which Development Scenarios? - Tao, M. (2013)
The Port of Sines “Terminal XXI” is an Iberian sea container harbour capable of accommodating vessels of the “Postpanamax” type. Located in the South of Portugal´s West Coast, “Terminal XXI” bears a unique location towards the Atlantic (37º57´N, 08º53´W), being the result of a thirty year-long public concession awarded to the Port of Singapore Authority (PSA) on a BOT model basis, in 2004. As a deep water port (16.5m ZH depth), Sines “Terminal XXI”, presents a capacity of handling 1.000.000 TEU´s per year, over a 730m long quayside, and includes a 24 ha (38,4 acre) storage surface. An expansion program is in due course at present, envisaging an increase of the container handling capacity to a level of 1.320.000 TEU´s per year, over a 940m long quayside, with a new configuration including nine “Postpanamax” and “Super-Postpanamax” gantry cranes. Sines “Terminal XXI” presents itself as a logical and key Atlantic outlet to many Spanish Continental Communities, with a particular regard to Greater Madrid (Central Meseta) or Zaragoza (Aragon), with their major and central logistical hubs, known as “Puertos Secos” (dry ports). Being linked to the Portuguese national railway network, “Terminal XXI” relies however on a too lengthy and circuitous rail itinerary, with a new “cut-off” to be materialized before 2020, under the auspices of RTE-T (freight) “Corridor 16”. This scheme will provide Sines “Terminal XXI” with a much more direct rail link to Spain and remaining Europe than the present situation, consisting of a new section of conventional line, from Evora to Badajoz border, and through the Communities of Extremadura and Castilla-la-Mancha, as far as Manzanares, via Merida and Ciudad Real, where another leg from “Corridor 16” originating at the Port of Algeciras will join, with both sections merging, to follow subsequently over existing modernized routes to Madrid and Zaragoza dry ports. A long-term phase of development will see the appearance of a completely new rail freight route from Zaragoza to France, involving a Central Pyrenean Tunnel. This will not be a foreseeable reality before 2030. The Atlantic positioning of “Terminal XXI” acquires a particular importance in the wake of the Panama Canal widening. From 2014 onwards, it will be possible for the “Postpanamax” and “Super-Postpanamax” container carriers, to follow a new planetary route linking the emerging economies of Far East Asia and those of Western Europe, with a passage by North America´s East Coast, as an intermediate point. The economies of scale brought about by the new route, presenting itself as an alternative to the traditional Indic-Suez and Cape Horn-South America routes, is susceptible of originating a re-configuration of the pattern of “Postpanamax” vessel routes worldwide, with an increasing emphasis being conferred to the North Atlantic. Owing to its strategic positioning as a deep-water container port, Sines “Terminal XXI”, is a likely candidate, to become integrated into the new emerging global logistics network, but it is necessary to assess the extent to which it may be an active part of a complex web of sea routes and its operators, rail freight transport and inland final clients, either forwarding or receiving containerized goods. This paper aims to assess the likely developments of the Sines “Terminal XXI” container facility, presenting alternative development scenarios, set at three distinct periods: i) 2014-2020, during the first years after the widening of the Panama Canal; ii) 2020-2030, including the fully completion and bringing into commercial operation of the new RTE-T “Corridor 16” Rail Link; and iii) beyond 2030, contemplating the establishment of a Central Pyrenean Tunnel as an alternative to the historical and traditional rail links, via the Basque Country and Catalonia, and the widespread use of 1435mm standard-gauge tracks, replacing the 1668mm broad-gauge ones, currently existent on virtually all conventional (non-high speed) main line railways of the Iberian Peninsula. Recent proposals concerning the possible constitution of an American-EU Free-Trade Area on a medium-term period, further emphasize the likely importance of Sines “Terminal XXI”. Since the port of Sines presents a unique deep-water Atlantic container terminal in Western Europe, research results are expected to provide useful indicators for policy purposes, leading to more sustainable development patterns of global freight and logistics.